2001
DOI: 10.1055/s-2001-12429
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of 11β-Hydroxysteroid Dehydrogenase: Activity in the Placenta, Kidney, Colon of Fetal Rats and Rabbits

Abstract: Mechanisms to regulate closely fetal GC exposure are of considerable importance, as certain organs (kidney, brain) are adversely affected by excess GCs. 11beta-Hydroxysteroid dehydrogenase type 2 (11beta-HSD2) reduces transplacental passage of maternal GCs to the fetus. We hypothesized that 11beta-HSD2, if active in fetal kidney and colon, might allow local tissue modulation of GC access during the critical last trimester. We determined the presence, ontogeny and functionality of 11beta-HSD in the placenta and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The recent report of 11b HSD 1's role in fetal lung development by Hundertmark [1,2] has confirmed our earlier findings using contemporary techniques. The observation that knocking out the 11b HSD 1 gene gives a lung phenotype consistent with its role in fetal lung maturation and pulmonary surfactant production [3] is further confirmation of the earlier series of studies of its role in this critical process of fetal transition and viability cited in this commentary.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The recent report of 11b HSD 1's role in fetal lung development by Hundertmark [1,2] has confirmed our earlier findings using contemporary techniques. The observation that knocking out the 11b HSD 1 gene gives a lung phenotype consistent with its role in fetal lung maturation and pulmonary surfactant production [3] is further confirmation of the earlier series of studies of its role in this critical process of fetal transition and viability cited in this commentary.…”
supporting
confidence: 81%
“…
Hundertmark et al [1] recently reported that 11-oxo steroids, like their 11-hydroxy isoforms, can stimulate fetal lung maturation due to the expression of 11b-hydroxysteroid dehydrogenase Type 1 (11b HSD 1), the enzyme that converts (inactive) cortisone to (active) cortisol [2]. In a subsequent study, this group has shown that knocking out the 11b HSD 1 gene inhibits lung maturation and surfactant synthesis [3], confirming the biological significance of 11b HSD 1 in lung development.
…”
mentioning
confidence: 99%
“…The capacity of thymocytes to generate bioactive GCS may be especially important during fetal development, when placental and fetal tissue 11␤-HSD2 is functioning to inactivate maternal GCS, preventing any deleterious effects of bioactive GCS on the developing fetus (21,22,76). The 11-keto GCS-rich environment present throughout most of gestation would maximize the potential for thymocyte 11␤-HSD1 activities.…”
Section: Discussionmentioning
confidence: 99%
“…In early to mid gestation, 11␤-HSD2 is found throughout the kidney in the mouse (93), sheep (385), and human (285,673), notably in Bowman's capsule and the vascular tufts of the developing glomeruli as they migrate from the surface to the inner cortex (126). In late gestation, the expression pattern becomes more discrete with very high levels in the distal convoluted tubules and collecting ducts (93,126,127,307), resembling the adult pattern. Indeed, in the later stages of gestation, MR becomes colocalized with 11␤-HSD2, suggesting 11␤-HSD2 is protecting inappropriate activation of MR at this time, whereas at earlier time points 11␤-HSD2 may modulate glucocorticoid signaling through GR (93, 126).…”
Section: Fetal Kidneymentioning
confidence: 99%